2017
DOI: 10.1111/jvh.12748
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of vertical transmission of Hepatitis C virus in Pakistan in 2007 and 2012 birth cohorts

Abstract: SummaryDespite a combination of high Hepatitis C virus (HCV) prevalence, a large adult population and high fertility, no published estimates of the scale and contribution of vertical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Despite some suggestive evidence for community-based exposures [ 152 ], such as visiting roadside barbers [ 161 ], this mode of exposures remains to be clarified with concrete analytical studies. Though HCV vertical transmission appears to account for a quarter of HCV infections among children under 5 years of age in Pakistan [ 181 ], only one study appears to have investigated this mode of exposure in this country [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite some suggestive evidence for community-based exposures [ 152 ], such as visiting roadside barbers [ 161 ], this mode of exposures remains to be clarified with concrete analytical studies. Though HCV vertical transmission appears to account for a quarter of HCV infections among children under 5 years of age in Pakistan [ 181 ], only one study appears to have investigated this mode of exposure in this country [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are still gaps in our understanding of HCV epidemiology in this country. Conduct of a nationally-representative population-based survey is strongly recommended to provide a better estimate of HCV prevalence in the whole population, delineate the spatial variability in prevalence, identify specific modes of exposure, and assess HCV knowledge and attitudes, as has been recently conducted in Egypt 10 , 99 103 and Pakistan 6 , 15 , 104 .…”
Section: Discussionmentioning
confidence: 99%
“…We did not incorporate disease‐related mortality, but the relative risk of mortality with HCV infection is too small to affect significantly our projections . We did not explicitly factor mother to child transmission in the model, but the contribution of this mode of exposure is limited relative to the overall infection burden in Pakistan …”
Section: Discussionmentioning
confidence: 99%
“…While HCV epidemics appear to be contracting across countries globally, it has been suggested that Pakistan's epidemic may be bucking this trend with a growing epidemic . Different lines of evidence further suggest a high ongoing HCV incidence, driven possibly by various healthcare‐related procedures, such as reuse of injections, inadequate blood screening and deficient infection control, among others …”
Section: Introductionmentioning
confidence: 99%